Tissue-type plasminogen activator is a neuroprotectant in the central nervous system - Yepes, Manuel (Frontiers in Cellular Neuroscience, 2015)
Tissue-type plasminogen activator (tPA) is a serine proteinase found not only in the intravascular space but also in a well-defined sub-set of neurons in the brain. TPA is rapidly released from neurons after either exposure to hypoxia or hypoglycemia in vitro, or the induction of cerebral ischemia in vivo. It has been proposed that tPA has a neurotoxic effect in the ischemic brain. However, recent evidence indicate that once released in the synaptic cleft tPA activates specific cell signaling pathways that promote the detection and adaptation to metabolic stress. More specifically, the non-proteolytic interaction of tPA with N-methyl-D-aspartate receptors (NMDARs) and a member of the low-density lipoprotein receptor (LDLR) family in dendritic spines activates the mammalian target of rapamycin (mTOR) pathway that adapts cellular processes to the availability of energy and metabolic resources. TPA-induced mTOR activation in neurons leads to hypoxia-inducible factor - 1α (HIF-1α) accumulation, HIF-1α-induced expression and membrane recruitment of the neuronal transporter of glucose GLUT3, and GLUT3-mediated uptake of glucose. These and other data discussed in this Review suggest that the postulated neurotoxic effect of tPA needs to be reconsidered and instead indicate the emergence of a new paradigm: that tPA is an endogenous neuroprotectant in the central nervous system.